Sexual dimorphism of body size in an African fossil ape, Nacholapithecus kerioi. Issue 123 (October 2018) - Kikuchi, Yasuhiro; Nakatsukasa, Masato; Tsujikawa, Hiroshi; Nakano, Yoshihiko; Kunimatsu, Yutaka; Ogihara, Naomichi; Shimizu, Daisuke; Takano, Tomo; Nakaya, Hideo; Sawada, Yoshihiro; Ishida, Hidemi
Abstract: Sexual size dimorphism in the African fossil ape Proconsul nyanzae (18 million years ago, 18 Ma) has been previously documented. However, additional evidence for sexual dimorphism in Miocene hominoids can provide great insight into the history of extant hominoid mating systems. The present study focused on body mass (BM) sexual dimorphism in Nacholapithecus kerioi from the Middle Miocene (16–15 Ma) in Africa. Bootstrap analysis revealed that P. nyanzae BM sexual dimorphism was lower than that in Pan troglodytes, which exhibits moderate sexual dimorphism, as reported previously. The same simulation revealed that BM sexual dimorphism of N. kerioi was comparable with that in Gorilla spp.; i.e., the males were approximately twice as large as the females. High sexual dimorphism in extant apes is usually indicative of a polygynous social structure (gorilla) or solitary/fission-fusion social system (orangutan). However, because of the high proportion of adult males in this fossil assemblage, the magnitude of dimorphism inferred here cannot be associated with a gorilla-like polygynous or oranguran-like solitary/fission-fusion social structure, and may reflect either taphonomic bias, or some other social structure. Extant hominoids have a long evolutionary history owing to their deep branching, comprising only a few existing members of the original highly successful group. Therefore, it is not surprising that the mating systems of extant hominoids fail to provide fossil apes with a perfect "model". The mating systems of extinct hominoids may have been more diverse than those of extant apes.